2023
DOI: 10.1371/journal.pmed.1004196
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and clinical outcomes of HBV reactivation in non-liver solid organ transplant recipients with resolved HBV infection: A systematic review and meta-analysis

Abstract: Background Current guidelines do not recommend routine antiviral prophylaxis to prevent hepatitis B virus (HBV) reactivation in non-liver solid organ transplant (SOT) recipients with resolved HBV infection, even in anti-hepatitis B surface antigen (anti-HBs)-negative recipients and those receiving intense immunosuppression. This systematic review and meta-analysis aimed to determine the incidence, risk factors, and clinical outcomes of HBV reactivation in non-liver SOT recipients. Methods and findings Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
3
3
Order By: Relevance
“…A metaanalysis of nonliver SOT recipients with past HBV infection showed that the incidence of HBVr was much lower compared to our study (3% vs. 12%) [14]. Furthermore, in the subgroup analysis of that meta-analysis, the incidence of HBVr was below 10% in all subgroups: induction with ATG (5%), history of acute rejection (6%), negative HBsAb (8%), and use of rituximab (8%) [14]. Our study might have a higher HBVr rate for several reasons compared to previous studies.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…A metaanalysis of nonliver SOT recipients with past HBV infection showed that the incidence of HBVr was much lower compared to our study (3% vs. 12%) [14]. Furthermore, in the subgroup analysis of that meta-analysis, the incidence of HBVr was below 10% in all subgroups: induction with ATG (5%), history of acute rejection (6%), negative HBsAb (8%), and use of rituximab (8%) [14]. Our study might have a higher HBVr rate for several reasons compared to previous studies.…”
Section: Discussioncontrasting
confidence: 88%
“…Antiviral prophylaxis is recommended when the risk of HBVr is >10%, but not when the risk is <1% [12]. A metaanalysis of nonliver SOT recipients with past HBV infection showed that the incidence of HBVr was much lower compared to our study (3% vs. 12%) [14]. Furthermore, in the subgroup analysis of that meta-analysis, the incidence of HBVr was below 10% in all subgroups: induction with ATG (5%), history of acute rejection (6%), negative HBsAb (8%), and use of rituximab (8%) [14].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In solid organ transplant (SOT) recipients, immunosuppression can result in HBV reactivation with ccc DNA serving as the replication template, which may further cause progressive hepatitis, hepatic failure, and even death. 11 HBV reactivation can occur in hepatocellular carcinoma (HCC) treatment such as transarterial chemoemblization (TACE), resection, and radiofrequency ablation (RFA). HBV reactivation after TACE in HCC treatment has been wellstudied.…”
Section: Discussionmentioning
confidence: 99%